Assessing the news literacy of public high school students - Kwan, Katrina S.; Agapito, Gabb Riel M.; Bascos, Shiela Camille V. (2008)
News literacy is having the ability to understand, evaluate, and make use of the news in different situations. Guided by Potter's Media Literacy Theory, this study assesses news literacy of public high school students nowadays. A total of 205 public high schools students, chosen using non-probability sampling, completed a self-administered questionnaire. Findings reveal that the respondents were generally aware of what news is. They selected and consumed news based on their personal interests and perceived importance. While they considered political news important, they did not consume much news about it since politics was not among their primary interests. Also, news for them had some relevance since they can use it especially in classroom-related activities. And as they handle variety of news, it can therefore be held that they are competent not only in news acquisition, but also in understanding and evaluating the news. Hence, as revealed by the findings in areas of news literacy, the authors regard the respondents as news literate.